Synthesis, Characterization and Antioxidant Evaluation of Some Tetrazole Derivatives - Meinaa Jaber Dalal; Athraa Hameed Mekky (Universitas Gadjah Mada, 2022)
The present study introduces the synthesis of two series of tetrazole derivatives. Firstly, monosubstituted S1 was prepared by the reaction of ethyl 4-aminobenzoate with an amount of sodium azide and triethyl orthoformate in hot glacial acetic acid. Then, ethyl 4-(1H-tetrazol-1-yl) benzoate S1 was treated with a solution of hydrazine hydrate to prepare acetohydrazide S2. After that, tetrazole derivatives S3-S4 were prepared via the reaction of acetohydrazide S2 with various aromatic aldehydes. Secondly, compound 1,5-disubstituted tetrazole S5 was prepared from the reaction of aryl isothiocyanate with sodium azide in water presence. Then alkylation to compound S5 was made with ethyl chloroacetate to produce S6. In the next step, S6 was reacted with hydrazine hydrate to get acetohydrazide S7. Moreover, the produced S7 was reacted with some aromatic aldehydes for the synthesis of S8-S10. The structures of synthesized compounds were confirmed by the different available spectral methods, i.e., FTIR, 1H-NMR and 13C-NMR spectroscopy. The antioxidant activity of the synthesized compounds was evaluated by the use of 2,2-diphenyl-1-picrylhydrazyl. The results showed that compound S10 has the highest value as radical scavenging among the synthesized compounds.